Efektivitas Media Flashcard Terhadap Keterampilan Menulis Kosakata Bahasa Inggris Siswa Sekolah Dasar - Lusi Nuryanti; Rina Mariana Hesti (JIP (Jurnal Intervensi Psikologi), 2022)
English writing skill in elementary schools show a lot of errors. Flashcard is used to improve English vocabulary writing skill. This study aims to determine the effectiveness of flashcard on English vocabulary writing skill of elementary school students. The study was conducted with a pre-experimental design type one group pretest - posttest design. The participants were third grade students, totaling 21 people. The data collection instrument was an English test. The study used pre-test and post-test. The data was processed by Paired t-test. It showed an increase in English test scores. English vocabulary writing errors decreased after the use of flashcard media. The results showed that flashcard media was effective in improving English vocabulary writing skills for elementary school students.